Innovation career guidance program management based on student career maturity in STEM Education at PTKIN - Gustini, Neng; Mulyani, Heny; Huwaida, Raden Luzna; Hafiz, Fadlan (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study explores the innovation of career guidance program management based on student career maturity within the context of STEM education at Islamic Higher Education Institutions (PTKIN). Employing a Systematic Literature Review (SLR) of 27 peer-reviewed articles published between 2015 and 2025, the research synthesizes global and national perspectives on STEM-oriented guidance, career maturity development, and the application of the CIPP evaluation model. The findings reveal that effective STEM career guidance management requires strategic integration of institutional planning, digital mentoring systems, and multi-stakeholder collaboration. Career maturity development in higher education is strengthened through experiential learning, mentoring, and curriculum-embedded career literacy. Furthermore, the adaptation of the CIPP framework enhances program accountability and continuous improvement. The study introduces three innovative contributions: the Strategic Alignment Model for program management, the Integrated Maturity Pathway (IMP) for student development, and the CIPP-STEM Evaluation Engine for adaptive assessment. Together, these frameworks establish a coherent model for managing STEM-based career guidance that aligns institutional missions with employability outcomes. The research advances theoretical and practical understanding of career education management in PTKIN and provides a replicable foundation for sustainable innovation in higher education.